'Feel-in-Touch!': Imagination through vibration: A utopia of vibro-acoustic technology, puppetry and multimedia art - Özcan, O (MIT PRESS, 2004)
This article introduces a conceptual design for an interactive artwork called Feel-in-Touch! Its aim is to improve the use of imagination in artworks using abstract images in the formats of interactive media and vibro-tactile aids. New technologies can visually realize every surrealistic narration we can imagine, but these technologies limit our perceptions by presenting only one way of imagining, instead of multiple alternatives. This restricts creative thinking. Working from the above assumption, this article explores how to increase the degree of imagination in an interactive artwork. The author discusses problems of the imagination in art and interactive media and summarizes current research on vibro-tactile and vibro-acoustic applications. He then outlines Feel-in-Touch! and discusses the outputs of this conceptual design.
Keywords: Art